1991
DOI: 10.1105/tpc.3.6.593
|View full text |Cite
|
Sign up to set email alerts
|

Plasmodesmatal function is probed using transgenic tobacco plants that express a virus movement protein.

Abstract: A gene encoding a temperature-sensitive mutant (MPP154A) of the 30-kilodalton movement protein (MP) of tobacco mosaic virus (TMV) was transformed into Nicotiana tabacum cv Xanthi. Transgenic plants expressing the MPP154A gene complemented local and systemic movement of an MP-defective mutant of TMV (U3/12MPfs) at the permissive temperature of 24 degrees C but not at 32 degrees C, the nonpermissive temperature. A microinjection procedure was used to investigate the effects of the modified TMV MP on plasmodesmat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
43
0
2

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(50 citation statements)
references
References 32 publications
5
43
0
2
Order By: Relevance
“…Among them are the overall area of the sieve plate together with the size and number of the pores within the sieve plate itself. Recent evidence (Wolf et al, 1991) confirms earlier studies showing the potential impact of callose ([ 1+3]-/3-~-glucan) accumulation in the regulation of both cell-to-cell and long-distance transport in plants. Deposition of this polysaccharide reduces the size-exclusion limit of the sieve-plate pore in sieve tubes and, hence, constricts the cell-to-cell movement within the strands.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Among them are the overall area of the sieve plate together with the size and number of the pores within the sieve plate itself. Recent evidence (Wolf et al, 1991) confirms earlier studies showing the potential impact of callose ([ 1+3]-/3-~-glucan) accumulation in the regulation of both cell-to-cell and long-distance transport in plants. Deposition of this polysaccharide reduces the size-exclusion limit of the sieve-plate pore in sieve tubes and, hence, constricts the cell-to-cell movement within the strands.…”
Section: Discussionsupporting
confidence: 76%
“…The enzyme may also have a key role in the synthesis of callose, a (1+3)-/3-~-glucan that is a common structural and/or storage polysaccharide in higher plants (McNairn and Cumer, 1968). Callose has been implicated in the plugging of sieve plates following injury to phloem and in controlling symplastic transport through its deposition in plasmodesmata (Wolf et al, 1991). Previous studies have shown that the preferred substrate for production of callose is UDP-Glc (Morrow and Lucas, 1987).…”
mentioning
confidence: 99%
“…It has been observed that heterologously expressed viral MPs upon microinjection can trigger an increase of the plasmodesmal SEL allowing the passage of dextran molecules with a molecular mass up to 10 kDa (Ding et al, 1995;Fujiwara et al, 1993;Noueiry et al, 1994;Waigmann and Zambrisky, 1995;Waigmann et al, 1994). Similar results were obtained for transgenic plants expressing the MPs of TMV (Deom et al, 1987(Deom et al, , 1990Ding et al, 1992;Wolf et al, 1989Wolf et al, , 1991, cucumber mosaic virus (CMV; Vaquero et al, 1994) and alfalfa mosaic virus (AMV; Poirson et al, 1993).…”
Section: Introductionsupporting
confidence: 71%
“…fluorescent probes Ͼ1000 Da and viral RNA) to pass from one cell to another. These observations of increase of SEL are based on pressure microinjection studies involving the injection of purified MPs (Ding et al, 1995;Fujiwara et al, 1993;Noueiry et al, 1994;Waigmann and Zambrisky, 1995;Waigmann et al, 1994), and injection of transgenic plants expressing the MP of TMV (Deom et al, 1987(Deom et al, , 1990Ding et al, 1992;Wolf et al, 1989Wolf et al, , 1991, CMV (Vaquero et al, 1994) and of AMV (Poirson et al, 1993). In this paper we have compared this broadly applied pressure injection technique with iontophoresis, which may represent an alternative injection technique to study the effect of plant viral MPЈs on plasmodesmal gating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation